2016
DOI: 10.1002/app.44354
|View full text |Cite
|
Sign up to set email alerts
|

Elastomeric foam prepared by supercritical carbon dioxide

Abstract: Biodegradable elastomer poly[(1,4‐butylene terephthalate)‐co‐(1,4‐butylene adipate)] foam was successfully prepared using supercritical CO2. The elastomer foam has closed and uniform cell structure with density about 90 g/L. Narrow size distribution with average cell diameter 32 μm were obtained. The foamed balls show rubbery properties and can recover well (>90%) to their original shape quickly after releasing press stress. Cell growth needs to take place at melting state where the migration and orientation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Though efforts have been made to increase nucleation, improve mechanical properties, remove skin layer, and improve foam expansion of TPU foams, study on reducing foam shrinkage has not been reported. TPU elastomer foams could undergo substantial foam shrinkage, like other elastomer and rubber foams . Typically, elastomers have T g that is well below T r , which can prevent T g from acting as the anchor point to fix the foamed structure.…”
Section: Introductionmentioning
confidence: 99%
“…Though efforts have been made to increase nucleation, improve mechanical properties, remove skin layer, and improve foam expansion of TPU foams, study on reducing foam shrinkage has not been reported. TPU elastomer foams could undergo substantial foam shrinkage, like other elastomer and rubber foams . Typically, elastomers have T g that is well below T r , which can prevent T g from acting as the anchor point to fix the foamed structure.…”
Section: Introductionmentioning
confidence: 99%
“…There are other complications; for example, a common phenomenon observed in the foaming of elastomers such as poly(1,4‐butylene terephthalate) ‐co‐ (1,4‐butylene adipate) is the post‐expansion of the polymer after removal from their foaming molds. This arises from the low (below room temperature) T g and the residual CO 2 remaining in the polymer which causes the further foaming at room temperature . In some other systems such as styrene‐ethylene‐butylene‐styrene (SEBS) elastomers and also in foams generated from poly(ethylene ‐co‐ octene), instead of postfoaming expansion, foam shrinkage is observed which is attributed to the elasticity of the polymer.…”
Section: Introductionmentioning
confidence: 99%